Physico-Chemical Properties and Phase Behavior of the Ionic Liquid-β-Cyclodextrin Complexes - Rogalski, Marek (MDPI, 2013)
The solubility of β-cyclodextrin (β-CD) in ionic liquids (ILs) and the activity coefficients at infinite dilution ( [Formula: see text]) of more than 20 solutes (alkanes, aromatic hydrocarbons, alcohols) were measured in four chosen ionic liquids, their mixtures with β-CD, and in the β-CD at high temperatures from 338 to 398 K using the inverse gas chromatography. The intermolecular interactions, inclusion complexes and the possible increasing of the solubility of β-CD in water using the IL are presented. The solubility of β-CD in ten chosen hydrophobic ILs at the temperature T = 423 K was detected. The solid-liquid phase diagrams (SLE) of {IL (1) + β-CD (2)} binary systems at the high mole fraction of the IL were measured for three systems (1-ethyl-3-methylimidazolium chloride, [EMIM][Cl], 1-ethyl-3-methylimidazolium bromide, [EMIM][Br]; and for 1-butyl-3-methylimidazolium chloride, [BMIM][Cl]). The eutectic points were determined at the high IL concentration for all binary systems. The intermolecular interaction and the possibility of inclusion complexes of the IL and/or solvents with β-CD were discussed. The infrared spectroscopy, IR was used for the description of the intermolecular interactions in the (β-CD + IL) systems. It was shown via the activity coefficients at infinite dilution results that the inclusion complexes are dependent on the temperature. The addition of β-CD to the IL does not improve the selectivity of the separation of the aliphatics from aromatics.